Antibacterial activity and major constituents of Polyalthia cinnamomea basic fraction - Puteri I.A.M.Mahmud,; Wan A. Yaacob,; Nazlina Ibrahim,; Muntaz Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Polyalthia cinnamomea Hook.f. & Thomson (Annonaceae) or locally known as ‘Larak Batu Bukit’, ‘Pisang-pisang’, ‘Sugao’ and ‘Sigumpet Hutan’ is a small woody plant found throughout Malaysia and Singapore. In this study, the basic chemical components from the leaves of the plant were fractionated and the antibacterial activity as well as the major constituents of the basic fraction was determined. To the best of our knowledge, this is the first study being carried out on the bioactivity and phytochemistry of P. cinnamomea. The basic fraction remarkably inhibited the growth of ten bacteria tested except one. The biggest inhibitory diameter and the lowest minimum inhibitory concentration were 19.0±4.6 mm and 0.125 mg/mL against respective Bacillus subtilis and Bacillus thuringiensis. Gas chromatography-mass spectrometry (GCMS) analysis of the basic fraction identified four major cyclosiloxanes of octamethylcyclotetrasiloxane (18.1%), decamethylcyclopentasiloxane (16.4%), dodecamethylcyclohexasiloxane (14.1%) and tetradecamethylcycloheptasiloxane (6.0%). The knowledge of the antibacterial potential of P. cinnamomea basic fraction and the major constituents present in the fraction can be utilized in the fields of natural products, pharmaceutical, cosmetic and personel care industries.